Evaluating Smartphone Addiction Disorder among University Students - Subramaniam S.; Dhillon J.S.; Kah Hoe A.C.; Shanmugam M.; Gunasekaran S.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Factor analysis; Students; Exploratory Factor Analysis (EFA); Neck pains; Online class; Online meetings; Quantitative study; Sleep disorders; University students; Video calls; Smartphones